The non-anthropocentric informational agents: Codes, software, and the logic of emergence in cybersecurity - Fouad, Noran Shafik (Review of international studies, 2022)
Many theoretical approaches to cybersecurity adopt an anthropocentric conceptualisation of agency; that is, tying the capacity to act to human subjectivity and disregarding the role of the non-human in co-constructing its own (in)security. This article argues that such approaches are insufficient in capturing the complexities of cyber incidents, particularly those that involve self-perpetuating malware and autonomous cyber attacks that can produce unintentional and unpredictable consequences. Using interdisciplinary insights from the philosophy of information and software studies, the article counters the anthropocentrism in the cybersecurity literature by investigating the agency of syntactic information (that is, codes/software) in co-producing the logics and politics of cybersecurity. It specifically studies the complexities of codes/software as informational agents, their self-organising capacities, and their autonomous properties to develop an understanding of cybersecurity as emergent security. Emergence is introduced in the article as a non-linear security logic that captures the peculiar agential capacities of codes/software and the ways in which they challenge human control and intentionality by co-constructing enmity and by co-producing the subjects and objects of cybersecurity.